On Identically Distributed non-Volterra Cubic Stochastic Operator - Jamilov, U. U.; Ladra, M. (Journal of Applied Nonlinear Dynamics, 2026)
We introduce the notion of identically distributed strictly non-Volterra cubic stochastic operator. We show that any identically distributed strictly non-Volterra cubic stochastic operator has a unique fixed point and that such operator has the property of being regular.